Interactive Learning Media through Nearpod to Increase the Economic Literacy of Students at the High School Level - Muhammad Hasan; A. Anugrawati; Nurjannah; Andi Tenri Ampa; Muhammad Ihsan Said Ahmad (Jurnal Edutech Undiksha, 2024)
The learning process in schools is still focused on teachers, and most use conventional learning media, so students are less involved in learning, and students' interest in learning has also decreased. This research aims to develop interactive learning media through Nearpod to increase the economic literacy of participants at the high school level. The research method used is the Research & Development (R&D) method, or developing a product with a comparative and percentage research design. The research stages are based on the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects were senior high school students, the research sample was 22 students and was selected using a purposive sampling technique. The data collection techniques used were observation, interviews, and administering questionnaires and tests. The results of this research show that the interactive learning media developed through Nearpod, namely "Slide of Cashless,” is very feasible to develop, interesting in using learning media, and effective in increasing the economic literacy of students at the high school level. This research supports and strengthens the findings from previous studies. The results of this research also prove that using Nearpod as an interactive learning medium in the learning process can increase students' economic literacy.